2019
DOI: 10.1007/978-3-030-05861-6_36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatments on Fatigue Properties of Ti–6Al–4V and 316L Produced by Laser Powder Bed Fusion in As-Built Surface Condition

Abstract: Over the last decade, additive manufacturing (AM) techniques have been expanding rapidly due to their ability to produce complex geometries with an efficient use of material. In order to design reliable AM parts, the mechanical properties resulting from the manufacturing process need to be understood. The present study investigates the fatigue of AM Ti-6Al-4V and 316L. Miniaturized Ti-6Al-4V and 316L specimens were manufactured using laser powder bed fusion (L-PBF). The geometry, process parameters, and loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…It could be noticed from the graph that the fatigue limit is at around 657 MPa (5x10 -6 cycles). This results is very much comparable or even better than cast Ti-6Al-4V results reported in Li et al [2] and one of the best that could be seen from literature for L-PBF processed Ti-6Al-4V [2,3].…”
Section: Fatigue Testssupporting
confidence: 87%
See 2 more Smart Citations
“…It could be noticed from the graph that the fatigue limit is at around 657 MPa (5x10 -6 cycles). This results is very much comparable or even better than cast Ti-6Al-4V results reported in Li et al [2] and one of the best that could be seen from literature for L-PBF processed Ti-6Al-4V [2,3].…”
Section: Fatigue Testssupporting
confidence: 87%
“…Therefore the combination of robust, repeatable part quality and tailored heat treatment provide good fatigue properties. Cutolo et al [3] reports this finding and even concludes that the SR treatment helps in achieving a better fatigue properties than HIP. The other important parameter for fatigue properties is surface roughness.…”
Section: Fatigue Testsmentioning
confidence: 85%
See 1 more Smart Citation
“…This geometry was used in other published and internal studies, and no significant deviations were found in the fatigue behaviour compared with standard-sized samples. [28][29][30][31] Highly stressed volume approach as mentioned by Van Hooreweder et al 32 was utilised in designing the sample geometry. This design ensures that maximum stress is concentrated at the gauge section while maintaining fatigue notch factor K f of unity.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies on the mechanical properties like hardness, tensile, and fatigue of SLM samples before and after solution heat treatment have been carried out by different authors (Ref 12,20,21). In addition, hot isostatic pressing (HIP) treatment also was applied on as-built SLM samples in numerous studies to improve the fatigue property of the SLM part and reduce porosity (Ref 22,23). However, combination of HIP with different post-heat treatments on the microstructure and mechanical properties of SLM specimens, aimed at improving structural integrity, microstructural and mechanical capability for different applications, has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%